\(x^8\)  - x = 0 

b) \(x^6\)...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 10 2022

hỏi thì hỏi cho đúng lớp chứ em nhỉ???

a, x8 - x = 0

⇔  x ( x7 - 1) = 0

⇔ \(\left[{}\begin{matrix}x=0\\x^7-1=0\end{matrix}\right.\)

⇔ \(\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)

b, x6 : x4 = 1

    x2 = 1

   x = +- 1

c, 4.x3 + 12 = 120

      x3 + 3 = 30

      x3 = 30 - 3

     x3 = 27

      x = 3

d, (2.x + 1).3 = 9.81

    2x + 1 = 9.81:3

    2x + 1 = 243

   2x = 243 - 1

    2x = 242

      x = 242 : 2

     x = 122

e, 5.x2 - 6 = 74

    5. x2 = 74 + 6

   5.x2 =80

      x2 = 80 : 5

      x2 = 16

    x = +- 4

13 tháng 7 2018

a) (1,5 . 1,9 - x - 0,5) : 0,25 = 7,5 : 0,125

=> (2,85 - x - 0,5) : 0,25 = 60

=> (2,85 - 0,5) - x = 60 . 0,25

=> 2,35 - x = 15

=> x = 2,35 - 15

=> x = -12,65

Vậy x = -12,65

b) \(1-\left(5\frac{2}{9}+x-7\frac{7}{18}\right)\div2\frac{1}{6}=0\)

\(\Rightarrow\left(5\frac{2}{9}-7\frac{7}{18}+x\right)\div2\frac{1}{6}=1-0\)

\(\Rightarrow\left(\frac{47}{9}-\frac{133}{18}+x\right)\div2\frac{1}{6}=1\)

\(\Rightarrow\frac{-13}{6}+x=2\frac{1}{6}\)

\(\Rightarrow x=2\frac{1}{6}-\frac{-13}{6}\)

\(\Rightarrow x=\frac{13}{6}+\frac{13}{6}\)

\(\Rightarrow x=\frac{26}{6}\)

\(\Rightarrow x=\frac{13}{3}\)

Vậy \(x=\frac{13}{3}\)

c) \(35\left(2\frac{1}{5}-x\right)=32\)

\(\Rightarrow2\frac{1}{5}-x=32\div35\)

\(\Rightarrow\frac{11}{5}-x=\frac{32}{35}\)

\(\Rightarrow x=\frac{11}{5}-\frac{32}{35}\)

\(\Rightarrow x=\frac{9}{7}\)

Vậy \(x=\frac{9}{7}\)

d) \(\frac{4}{3}+\left(x\div2\frac{2}{3}-0,5\right).1\frac{35}{55}=0,6\)

\(\Rightarrow\left(x\div\frac{8}{3}-\frac{1}{2}\right).\frac{18}{11}=\frac{3}{5}-\frac{4}{3}\)

\(\Rightarrow\left(x\div\frac{8}{3}-\frac{1}{2}\right).\frac{18}{11}=\frac{-11}{15}\)

\(\Rightarrow x\div\frac{8}{3}-\frac{1}{2}=\frac{-11}{15}\div\frac{18}{11}\)

\(\Rightarrow x\div\frac{8}{3}-\frac{1}{2}=\frac{-121}{270}\)

\(\Rightarrow x\div\frac{8}{3}=\frac{-121}{270}+\frac{1}{2}\)

\(\Rightarrow x\div\frac{8}{3}=\frac{7}{135}\)

\(\Rightarrow x=\frac{7}{135}.\frac{8}{3}\)

\(\Rightarrow x=\frac{56}{405}\)

Vậy \(x=\frac{56}{405}\)

e) \(1\frac{1}{3}.2\frac{2}{4}\div\frac{5}{6}.1\frac{1}{11}=11-5\div x\)

\(\Rightarrow\frac{4}{3}.\frac{5}{2}\div\frac{5}{6}.\frac{12}{11}=11-5\div x\)

\(\Rightarrow\frac{10}{3}\div\frac{5}{6}.\frac{12}{11}=11-5\div x\)

\(\Rightarrow4.\frac{12}{11}=11-5\div x\)

\(\Rightarrow11-5\div x=\frac{48}{11}\)

\(\Rightarrow5\div x=11-\frac{48}{11}\)

\(\Rightarrow5\div x=\frac{73}{11}\)

\(\Rightarrow x=5\div\frac{73}{11}\)

\(\Rightarrow x=\frac{55}{73}\)

Vậy \(x=\frac{55}{73}\)

a) (1,5 * 1,9 - x - 0,5) : 0,25 = 7,5 : 0,125

(2,85 - x - 0,5) : 0,25 = 60

(2,85 - x - 0,5) = 60 x 0,25

(2,85 - x - 0,5) = 15

2,35 - x = 15

x = 2,35 - 15

x = -12,65

\(\left(a\right)\frac{34-x}{30}=\frac{5}{6}\)

\(\frac{34-x}{30}=\frac{25}{30}\)

34 - x = 25

x = 34 - 25 = 9

\(\left(b\right)\frac{x+13}{34}=\frac{12}{17}\)

\(\frac{x+13}{34}=\frac{24}{34}\)

x + 13 = 24

x = 24 - 13 = 11

\(\left(c\right)\left(x+\frac{1}{3}\right)+\left(x+\frac{1}{9}\right)+\left(x+\frac{1}{27}\right)+\left(x+\frac{1}{81}\right)=\frac{56}{81}\)

\(4x+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}=\frac{56}{81}\)

Đặt \(A=\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}\)

Ta có : \(3A=1+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}\)

\(3A-A=1+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}-\frac{1}{3}-\frac{1}{9}-\frac{1}{27}-\frac{1}{81}\)

\(2A=1-\frac{1}{81}=\frac{80}{81}\)

\(A=\frac{80}{81}\div2=\frac{40}{81}\)

\(\Rightarrow4x+\frac{40}{81}=\frac{56}{81}\)

\(4x=\frac{56}{81}-\frac{40}{81}\)

\(4x=\frac{16}{81}\)

\(x=\frac{16}{81}\div4=\frac{4}{81}\)

9 tháng 8 2020

a, \(\frac{34-x}{30}=\frac{5}{6}\Leftrightarrow\frac{34-x}{30}=\frac{25}{30}\)

\(\Leftrightarrow34-x=25\Leftrightarrow x=9\)

b, \(\frac{x+13}{34}=\frac{12}{17}\Leftrightarrow\frac{x+13}{34}=\frac{24}{34}\)

\(\Leftrightarrow x+13=24\Leftrightarrow x=11\)

13 tháng 9 2017

\(x+\frac{15}{7}=\frac{9}{2}\)

\(x=\frac{9}{2}-\frac{15}{7}=\frac{33}{14}\)

\(x-\frac{3}{4}=\frac{7}{2}\)

\(x=\frac{7}{2}+\frac{3}{4}=\frac{17}{4}\)

\(x.\frac{7}{8}=\frac{12}{5}\)

\(x=\frac{12}{5}:\frac{7}{8}=\frac{96}{35}\)

\(\frac{5}{6}:x=\frac{4}{3}\)

\(x=\frac{5}{6}:\frac{4}{3}=\frac{5}{8}\)

13 tháng 9 2017
  • a) x=9/2-15/7=33/14
  • b) x=7/2+3/4=17/4
  • c) x=12/5:7/8=61/35
  • d) x=5/6:4/3=5/8
  • k nha
16 tháng 7 2017

a, 3/4 + 1/4.x=2

    1/4.x        = 2-3/4

     1/4.x      =5/4

     x           = 5/4:1/4

     x           = 5

     

16 tháng 7 2017

b, x-2/3.9/4=2,5-1/2

    x-2/3.9/4=2

    x-2/3     =2:9/4

    x-2/3   =8/9

     x        = 8/9+2/3

     x         = 14/9

    

21 tháng 6 2018

a)13x3x32,27+67,63x39

=39x32,27+67,63x39

=39x(32,27+67,63)

=39x100

=3900

21 tháng 6 2018

b,= 1- [ 1/2 x 1/3 x1/4 x..... x 1/100 ]

=1/2 x 2/3 x 3/4 x .......x 99/100

= 1x2x3x......x99 / 2x3x4x...... x100 [ rút gọn ]

= 1/100